(untitled) (Journal of Misan Researches, 2023)
In the twenty-first century, Turkey pursued a policy of expansion and influence to have an influential and active role in the international arena. Our research deals with this Turkish influence in Somalia after 2011, the year that contributed to opening new horizons for the development of bilateral relations between Turkey and Somalia in various fields, and influence by taking advantage of the Turkish government. An opportunity for the world to be preoccupied with international silence about the famine and drought crisis that affected Somalia and claimed the lives of thousands of victims in 2011, so that that year would usher in the welcome Turkish influence in Somalia after President Erdogan visited Mogadishu at the head of a large delegation sympathetic to the Somali people, offering hundreds of tons of food. This resulted in deepening cooperation between the two countries and consolidating and documenting Turkish political, diplomatic, economic and military influence in Somalia.